The Epidemiology of Various Intestinal Obstruction Causes in Children and Teenagers: A Multi-Center Study - Nazir Shah, Amir Muhammad, Atta Muhmmad Khan, Naeem Jan, Sijad Ur Rehman, Mohummad Qasim Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: to assess the Epidemiology of intestinal obstruction in children And Teenagers its causes. Study design: This is A Multicenter study. Place and duration of study: This study was conducted in lrh and hmc territory care hospital of kpk . Analysis was completed in 01 year, from Jan 2021 to Jan 2022. Methodology: This study included all children aged 13 to 18 years hospitalized in the pediatrics department who had an exploratory laparotomy for intestinal blockage and met the inclusion criteria. During an exploratory laparotomy, adhesions, intussusceptions, roundworms, and an obstructed hernia were identified as possible reasons for intestinal blockage. Software SPSS version 24 was used to analyze the data that was collected. We calculated percentages, means, and standard deviations. Results: 85 patients in all, including 30 cases (35% females) and 55 points (65% males), were analyzed. From [01] to [12] years was the range of ages, with a mean age of [04.3602.06] years. Adhesions were the most frequent cause of intestinal obstruction, followed by intussusception in 36 (42% of cases) and 27 (31% of cases), respectively. Conclusion: The prevalence of the etiological reasons for intestinal blockage in children And Teenagers varies by age group, although adhesions are the most frequent cause, with intussusception coming in second. Keywords: Children ,Teenagers, etiological causes, intestinal obstruction, adhesion, and intussusception